The Cooperative Establishment Program as a Capital Solution for Fishermen in Surabaya - Shochrul Rohmatul Ajija; Muryani Muryani; Sylva Alif Rusmita (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
This community service activity aims to provide training and assistance to the Nambangan and Cumpat fishermen group at KedungCowek Village, Kenjeran Sub-district, Surabaya. These programs are focused on solving the management problems of a fishermen cooperative. Fishermengroups are given training for establishing the cooperative legal entity and assistance for preparing the establishment documents. These fishermen group’s training and assistance activities are considered effective in solving management problems in a cooperative way by the fishermen group named Koperasi 64 Bahari Surabaya. The result of this program is the collection of documents for the establishment of a cooperative legal entity at the Koperasi 64 Bahari Surabaya. These programs also increase the trust of the Nambanganand Cumpat fishermen groups towards the cooperative. It is evidenced by the significant increase in total member savings since December 2019.